А)
х+у= -14
ху= -32
х= - 14-у
у(-14-у)= -32
х=-14-х
-14у-у²+32=0
у²+14у--32=0
D/4=7²+32=81=±9²
у1= -7-9= -16
у2= -7+9=2
у1= -16 у2=2
х1=-14-(-16) х2= -14-2
у1= -16 у2=2
х1= 2 х2= - 16
б)
х+у= -18
ху=65
х= -18 -у
у( -18 -у)=65
х= -18 -у
у²+18у+65=0
D/4=9²-65=16=±4²
у1= -9 -4= -13
у2= -9+4= -5
у1= -13 у2= -5
х1= -18 -( -13) х2= -18 -( -5)
у2= -13 у2= -5
х1= - 5 х2= - 13
в)
х-у=1
ху=72
х=1+у
у(1+у)=72
х=1+у
у²+у-72=0
D=1+4*72=289=±17²
у1=( -1 -17)/2= -9
у2=( -1+17)/2=8
у1= -9 у2=8
х1=1+(-9) х2=1+8
у1= -9 у2=8
х1= -8 х2=9
г)
х+у= -12
х-у= -2
2х=-14
у=х+2
х= - 7
у= -7+2
х= -7
у= -5